THE IMPORTANCE AND THE MEANINGS OF INDEPENDENT LEARNING: UNIVERSITY STUDENTS’ PERCEPTIONS - Dwi Agustina; Dwi Ario Fajar (Vidya Karya, 2018)
Abstract.  This article presents the findings of a qualitative study conducted in English Department of Pekalongan University in 2018. The study aimed at revealing students’ and teachers’ perceptions about the importance and the meanings of independent learning particularly in their language learning. However this article only reports the interview results with fourteen students. The findings signal the students’ positive perceptions about independent learning. All students considered independent learning as important to improve their mastery of English. They also presented various reasons on the importance of doing independent learning. Interestingly, while all students reported the importance of doing independent learning, they described independent learning with a range of meanings. This suggests that independent learning means different thing for different students. Among the meanings they give to independent learning covers: 1) individual effort to improve the language competence, 2) individuals’ learning habits, 3) independent learning activities, 4) self-evaluation activity, and 5) self-reflection activity. Key words: qualitative study, independent learning, perceptions